Visceral leishmaniasis: an unexpected diagnosis during the evaluation of pancytopenia in a kidney transplant recipient - Pêgo,C (2013)
The aetiological study of cytopenia in solid organ transplant recipients could be challenging, given the need to exclude infectious disorders, drug toxicity or neoplastic disease. Visceral leishmaniasis is endemic in several regions of the world, but a rare complication after renal transplantation (less than 100 cases described in literature). We report the case of a male renal transplant recipient, 57 years of age, admitted to our Unit 17 months after transplantation with febrile illness and severe pancytopenia. He had a history of leucopenia and thrombocytopenia detected in follow-up exams two months earlier, with progressive worsening despite discontinuation of drugs with potential haematologic toxicity. On admission, his complaints were weakness, night sweats and weight loss. On examination, he was febrile, pale, and had a palpable spleen. Laboratory exams demonstrated: leukocytes 1.1 x109/L, platelets 68 x109/L, haemoglobin 10.3 g/dl, serum creatinine 1.48 mg/dl, C-reactive protein 9.72 mg/dl. Abdominal ultrasound confirmed splenomegaly. A bone marrow aspiration was performed and antibiotic therapy was instituted empirically, without improvement. Additional laboratory results were inconclusive: negative blood and urine cultures, no evidence of cytomegalovirus, parvovirus B19 or HIV infections, hepatitis B and C and masses/ adenopathies were excluded by computerized tomography. Despite the absence of an evident epidemiological context, the bone marrow examination showed amastigotes of Leishmania spp. He was started on liposomal amphotericin B (4 mg/kg/day; total of 10 administrations) with a sustained clinical and laboratory improvement after the second day of therapy. Visceral leishmaniasis is a potentially lethal infection if treatment is delayed or not instituted. Although rare among renal transplant recipients it should be included in the differential diagnosis of febrile pancytopenia